Inhaled nitric oxide in fibrotic and advanced interstitial lung disease: A systematic review and meta-analysis of randomized controlled trials - Shun Nakahara; Yusuke Hirao; Bradley Fujiuchi; Brent Matsuda (PLoS ONE, 2026)
Purpose Interstitial lung disease (ILD) can lead to pulmonary hypertension (PH), contributing to reduced exercise capacity in patients with ILD. Inhaled nitric oxide (iNO) reduces pulmonary artery pressure and pulmonary vascular resistance and may improve exercise capacity in this population; however, the available evidence remains limited. Therefore, we conducted a systematic review and meta-analysis to compare the efficacy and safety of iNO versus placebo in patients with ILD. Methods We systematically searched PubMed, Embase, Cochrane databases, and ClinicalTrials.gov for randomized controlled trials (RCTs) comparing iNO with placebo in patients with ILD. The primary endpoint was 6-minute walk distance (6MWD). Secondary endpoint was moderate-to-vigorous physical activity (MVPA). Safety endpoint was any adverse events. Continuous endpoints were reported using mean differences (MDs) or standardized mean differences (SMDs), and binary endpoints were reported using risk ratios (RRs), all with 95% confidence intervals (CIs). Results Four RCTs, including one crossover trial, enrolling 274 patients were analyzed. Of these, 172 received iNO. The median follow-up period was 12 weeks. In the pooled analyses, iNO likely results in little to no difference in 6MWD compared with placebo (MD 1.83m; 95% CI −12.98 to 16.64; p = 0.81), and may result in little to no difference in any adverse events (RR 1.12; 95% CI 0.97 to 1.30; p = 0.12) and MVPA (SMD 0.32; 95% CI −0.93 to 1.56; p = 0.39). Conclusion INO did not demonstrate improvements in 6MWD or MVPA. These findings do not support routine use of iNO in this population.